Binder particles for all-solid-state battery, composition for all-solid-state battery, functional layer for all-solid-state battery, and all-solid-state battery
By using binder particles for all-solid state batteries with specific cohesion and average particle size, the problem of insufficient adhesion caused by the cohesion of binder particles in the prior art is solved, and the excellent battery characteristics of all-solid state batteries are achieved.
Patent Information
- Application Number
- CN202180006880.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-31
- Filing Date
- 2021-01-20
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2041-01-20
AI Technical Summary
When using existing binders to manufacture all-solid state batteries in dry form, poor fluidity of the binder particles leads to condensation, resulting in insufficient adhesion between the electrode active material particles and the solid electrolyte particles, which in turn affects the output characteristics and circulation characteristics of the battery.
The binder particles for all-solid state batteries having a specific cohesion degree and an average particle size are composed of a polymer, with a cohesion degree of 1% or more and less than 30%, a volume average particle size D50 is 10 μm or more and 100 μm or less, and preferably the glass transition temperature of the polymer is 50°C or more and 120°C or less.
Even under dry manufacturing conditions, the electrode active material particles and solid electrolyte particles in the functional layer can be well bonded, thereby improving the battery characteristics of the all-solid state battery, including output characteristics and cycle characteristics.
Smart Images

Figure BDA0003671892960000321
Abstract
Description
Technical Field
[0001] The present invention relates to binder particles for all-solid-state batteries, a composition for all-solid-state batteries, a functional layer for all-solid-state batteries, and an all-solid-state battery. Background Art
[0002] In recent years, the demand for lithium-ion batteries and other batteries has been increasing for various uses, including small household power storage devices, electric motorcycles, electric vehicles, and hybrid electric vehicles, in addition to mobile terminals such as mobile information terminals and mobile electronic devices.
[0003] As such uses become more widespread, it is required to further improve the safety of the battery. In order to ensure the safety of the battery, for example, an effective method is to prevent leakage of an organic electrolyte formed by dissolving an electrolyte in an organic solvent. On the other hand, the technology of making a battery (all-solid-state battery) having a solid electrolyte layer instead of a flammable organic electrolyte and all components being made of solids has been studied.
[0004] Specifically, an all-solid-state battery generally has a solid electrolyte layer as an electrolyte layer between the positive electrode and the negative electrode. Here, when making an all-solid-state battery, a binder is generally used. For example, an electrode is formed by providing an electrode active material layer in the solid electrolyte layer and on the current collector. In the electrode active material layer of the electrode, the purpose of using a binder is to bind components such as solid electrolyte particles and electrode active materials to prevent these components from detaching from battery components such as electrodes.
[0005] For example, in patent documents 1 to 3, it is described that a slurry composition for an electrode layer comprising an electrode active material, solid electrolyte particles, a prescribed binder, and a solvent (dispersion medium) is applied to a current collector and dried to form an electrode active material layer. In addition, it is described that a solid electrolyte layer is formed by applying a slurry composition for a solid electrolyte layer comprising solid electrolyte particles, a prescribed binder, and a solvent (dispersion medium) to an electrode active material layer and drying.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent document 1: Japanese Patent No. 6459691;
[0009] Patent Document 2: Japanese Patent Application Publication No. 2015-088486;
[0010] Patent document 3: International Publication No. 2016 / 136090. Summary of the invention
[0011] Problem that the invention aims to solve
[0012] However, in the above-mentioned prior art in which a slurry composition containing a solvent (dispersion medium) is used to form an electrode active material layer and a solid electrolyte layer (hereinafter, these layers are sometimes collectively referred to as "functional layers"), it is necessary to disperse the ingredients well in the slurry composition, and the operations such as coating and drying are complicated. There is still room for improvement in these aspects.
[0013] Here, as a technology capable of solving such a problem, for example, a technology of dry-mixing components constituting a functional layer and molding the obtained composition using a molding method such as hot pressing to form the functional layer is considered.
[0014] However, according to the research of the inventors, when using the above-mentioned existing binder to manufacture all-solid-state batteries in a dry manner, the binder particles produce agglomeration (adhesion) due to poor fluidity, and the adhesion with the electrode active material layer, the electrode active material particles in the solid electrolyte layer, and the solid electrolyte particles may not be sufficient. Therefore, in the all-solid-state battery manufactured using the binder, it is sometimes impossible to make the electrode active material particles and the solid electrolyte particles fully bonded to each other, and the battery characteristics such as output characteristics and cycle characteristics are insufficient.
[0015] Therefore, the object of the present invention is to provide binder particles for all-solid-state batteries, compositions for all-solid-state batteries, and functional layers for all-solid-state batteries, and all-solid-state batteries with excellent battery characteristics, which can obtain all-solid-state batteries with excellent battery characteristics even when all-solid-state batteries are manufactured by a dry process.
[0016] Solutions for solving problems
[0017] The present inventors have conducted intensive studies to achieve the above-mentioned object. As a result, the present inventors have found that the above-mentioned object can be achieved by using binder particles for all-solid-state batteries having a specific degree of aggregation and a specific average particle size, thereby completing the present invention.
[0018] That is, the purpose of the present invention is to advantageously solve the above-mentioned problems. The binder particles for all-solid-state batteries of the present invention are characterized in that they are composed of a polymer, have a cohesion degree of 1% or more and less than 30%, and a volume average particle size D50 of 10 μm or more and 100 μm or less. If binder particles for all-solid-state batteries having such a specific cohesion degree and a specific average particle size are used, even when the functional layer is made in a dry manner, the electrode active material particles and the solid electrolyte particles in the functional layer can be well bonded, and the battery characteristics of the obtained all-solid-state battery can be improved.
[0019] Here, in the present invention, the "aggregation degree" of the binder particles for an all-solid-state battery can be measured by the method described in Examples described later.
[0020] In addition, in the present invention, the "volume average particle size D50" of the binder particles for all-solid-state batteries means the particle size at which the cumulative volume calculated from the small diameter side reaches 50% in the particle size distribution (volume basis) measured by laser diffraction method, and can be measured by the method described in the examples described later.
[0021] In addition, the glass transition temperature of the polymer of the binder particles for all-solid-state batteries of the present invention is preferably 50°C or more and 120°C or less. By making the glass transition temperature of the polymer 50°C or more and 120°C or less, in the all-solid-state battery manufactured using the binder particles for all-solid-state batteries, it is possible to further prevent the decrease in adhesion caused by excessive agglomeration of the binder particles for all-solid-state batteries, and it is possible to further prevent the decrease in strength caused by the binder particles for all-solid-state batteries becoming too hard. Therefore, the battery characteristics of the all-solid-state battery can be further improved.
[0022] Here, in the present invention, the “glass transition temperature” of the polymer contained in the binder particles for an all-solid-state battery can be measured by the method described in Examples described later.
[0023] In addition, the binder particles for all-solid-state batteries of the present invention preferably contain ethylenically unsaturated acid monomer units in the polymer, and the content of the ethylenically unsaturated acid monomer units in the polymer is 1.5% by mass or more and less than 10% by mass. If the polymer contains ethylenically unsaturated acid monomer units in the above ratio, the battery characteristics of the all-solid-state battery can be further improved.
[0024] In addition, the preferred polymer of the binder particles for all-solid-state batteries of the present invention comprises an alkyl acrylate monomer unit having an alkyl chain with a carbon number of 4 or more and an alkyl methacrylate monomer unit having an alkyl chain with a carbon number of 4 or less, and the content ratio of the alkyl acrylate monomer unit having an alkyl chain with a carbon number of 4 or more in the above-mentioned polymer is 5% by mass or more and 40% by mass or less, and the content of the alkyl methacrylate monomer unit having an alkyl chain with a carbon number of 4 or less in the above-mentioned polymer is 5% by mass or more and 40% by mass or less. If the polymer contains an alkyl acrylate monomer unit having an alkyl chain with a carbon number of 4 or more in the above-mentioned ratio, then in the all-solid-state battery manufactured using the binder particles for all-solid-state batteries, the binder particles for all-solid-state batteries can be more closely fitted with the electrode active material particles and the solid electrolyte particles. Therefore, the battery characteristics of the all-solid-state battery can be further improved. In addition, if the polymer contains an alkyl methacrylate monomer unit having an alkyl chain with a carbon number of 4 or less in the above ratio, in an all-solid-state battery manufactured using the all-solid-state battery binder particles, the all-solid-state battery binder particles can be more closely attached to the electrode active material particles and the solid electrolyte particles, and the strength reduction caused by the binder particles becoming too hard can be further prevented. Therefore, the battery characteristics of the solid-state battery can be further improved.
[0025] In addition, the preferred polymer of the binder particles for all-solid-state batteries of the present invention comprises at least one monomer unit selected from nitrile-containing monomer units and aromatic vinyl monomer units. If the polymer comprises at least one monomer unit selected from nitrile-containing monomer units and aromatic vinyl monomer units, it is possible to further prevent the adhesion reduction caused by excessive agglomeration of the binder particles for all-solid-state batteries and further prevent the strength reduction caused by the binder particles for all-solid-state batteries becoming too hard. Therefore, the battery characteristics of the all-solid-state battery can be further improved.
[0026] In addition, the preferred polymer of the binder particles for all-solid-state batteries of the present invention includes a cross-linking monomer unit, and the content ratio of the cross-linking monomer unit in the polymer is 0.1% by mass or more and less than 2.0% by mass. If the polymer includes a cross-linking monomer unit in the above ratio, the polymer is appropriately cross-linked, and the binder particles have an appropriate amount of gel structure, so that the excessive aggregation of the binder particles for all-solid-state batteries can be further prevented, and the strength reduction caused by the binder particles for all-solid-state batteries becoming too hard can be further prevented. Therefore, the battery characteristics of the all-solid-state battery can be further improved.
[0027] Furthermore, the object of the present invention is to advantageously solve the above-mentioned problems, and the composition for all-solid-state batteries of the present invention is characterized in that it contains any one of the above-mentioned all-solid-state battery binder particles and solid electrolyte particles. According to the composition for all-solid-state batteries containing the above-mentioned all-solid-state battery binder particles, a functional layer can be well formed, so that the all-solid-state battery can exert excellent battery characteristics.
[0028] In addition, the composition for an all-solid-state battery of the present invention preferably further comprises an electrode active material. If the electrode active material is contained, an electrode active material layer can be well formed, and the all-solid-state battery can exhibit excellent battery characteristics.
[0029] In addition, the all-solid-state battery composition of the present invention preferably further comprises a conductive aid. If the all-solid-state battery composition containing the electrode active material further comprises a conductive aid, the conductivity of the obtained electrode can be improved, and the battery characteristics of the all-solid-state battery can be further improved.
[0030] Furthermore, the object of the present invention is to advantageously solve the above-mentioned problems, and the functional layer for an all-solid-state battery of the present invention is characterized in that it is formed using any one of the above-mentioned all-solid-state battery compositions. The functional layer formed using the all-solid-state battery composition containing the above-mentioned all-solid-state battery binder particles can enable the all-solid-state battery to exert excellent battery characteristics.
[0031] Furthermore, the purpose of the present invention is to advantageously solve the above-mentioned problems, and the all-solid-state battery of the present invention is characterized in that it has the above-mentioned all-solid-state battery functional layer. The all-solid-state battery having the all-solid-state battery functional layer manufactured using the above-mentioned all-solid-state battery binder particles has excellent battery characteristics.
[0032] Effects of the Invention
[0033] According to the present invention, it is possible to provide binder particles for all-solid-state batteries, compositions for all-solid-state batteries, and functional layers for all-solid-state batteries, and all-solid-state batteries that can produce all-solid-state batteries with excellent battery characteristics even when all-solid-state batteries are manufactured in a dry process. DETAILED DESCRIPTION
[0034] The embodiments of the present invention are described in detail below.
[0035] The binder particles for all-solid-state batteries of the present invention (hereinafter also referred to as "binder particles") are used to manufacture all-solid-state batteries (e.g., to form functional layers). The composition for all-solid-state batteries of the present invention at least comprises the binder particles for all-solid-state batteries of the present invention and solid electrolyte particles, and is used to form the functional layers contained in the all-solid-state batteries. The functional layers for all-solid-state batteries of the present invention are formed by the composition for all-solid-state batteries of the present invention. Moreover, the all-solid-state battery of the present invention has the functional layers for all-solid-state batteries of the present invention.
[0036] (Binder particles)
[0037] The binder particles of the present invention are composed of a polymer, have a cohesion degree of 1% or more and less than 30%, and a volume average particle size D50 of 10 μm or more and 100 μm or less. The binder particles of the present invention are particles existing in a gas phase in a granular form, and usually exist as an aggregate of a plurality of particles.
[0038] In addition, the binder particles may contain additives, impurities mixed in during the manufacturing process, etc. However, the binder particles generally do not contain active materials or solid electrolytes.
[0039] (Properties of Binder Particles)
[0040] <Degree of cohesion>
[0041] The cohesion degree of the binder particles of the present invention needs to be 1% or more and less than 30%, preferably 1.5% or more, more preferably 2% or more, further preferably 10% or more, in addition, preferably 20% or less, more preferably 15% or less. By making the cohesion degree of the binder particles 1% or more and less than 30%, it is possible to exert good cohesion resistance (anti-adhesion), uniformly dry mix with electrode active material particles and / or solid electrolyte particles, and the binder particles will be well fitted with electrode active material particles and / or solid electrolyte particles. When the cohesion degree of the binder particles is less than 1%, it is impossible to fit well with the electrode active material particles and / or solid electrolyte particles, and the cycle characteristics of the all-solid-state battery are reduced. On the other hand, when the cohesion degree of the binder particles is 30% or more, the binder particles are excessively coagulated with each other, and the fluidity (dispersibility) during dry mixing is reduced. Therefore, the adhesion with the electrode active material particles and / or solid electrolyte particles is reduced, and the cycle characteristics are reduced.
[0042] The degree of aggregation of the binder particles can be controlled by, for example, adjusting the glass transition temperature of the polymer described below and / or the content ratio of the crosslinkable monomer unit contained in the polymer.
[0043] <Volume average particle size D50>
[0044] The volume average particle size D50 of the binder particles of the present invention needs to be more than 10 μm and less than 100 μm, preferably more than 15 μm, more preferably more than 20 μm, and more preferably more than 50 μm. In addition, it is preferably less than 90 μm, more preferably less than 85 μm, and more preferably less than 80 μm. When the volume average particle size D50 is less than 10 μm, the bonding area (particle coating area) with the electrode active material particles and the solid electrolyte particles is excessively increased, so the resistance increases. Therefore, the output characteristics of the all-solid-state battery are reduced. On the other hand, when the volume average particle size D50 is greater than 100 μm, the bonding area with the electrode active material particles and the solid electrolyte particles is reduced, so the adhesion is reduced. Therefore, the cycle characteristics of the all-solid-state battery are reduced.
[0045] In addition, the volume average particle diameter D50 can be set within a desired range by adjusting, for example, the amount of an emulsifier, the amount of a monomer, etc. in a polymer synthesis method described later. Alternatively, the volume average particle diameter D50 can be set within a desired range by using a particle size distribution adjustment method described later.
[0046] <Water content>
[0047] The moisture content of the binder particles of the present invention is preferably 10000 ppm or less, more preferably 5000 ppm or less, further preferably 2000 ppm or less, and particularly preferably 1000 ppm or less. When the moisture content is greater than 10000 ppm, there is a risk that the binder particles are easily condensed (adhesive) due to moisture, and the output characteristics and / or cycle characteristics of the all-solid-state battery are reduced.
[0048] The moisture content of the binder particles can be measured by the method described in Examples below.
[0049] (polymer)
[0050] <Glass transition temperature>
[0051] The glass transition temperature of the polymer constituting the binder particles of the present invention is preferably 50°C or more, more preferably 60°C or more, and further preferably 75°C or more. In addition, it is preferably 120°C or less, more preferably 110°C or less, and further preferably 100°C or less. If the glass transition temperature of the polymer is 50°C or more, it is possible to further prevent the excessive aggregation of the binder particles, prevent the decrease in adhesion with the electrode active material and the solid electrolyte particles, and thus prevent the resulting decrease in the cycle characteristics of the all-solid-state battery. In addition, if the glass transition temperature of the polymer is 120°C or less, it is possible to further prevent the binder particles from becoming too hard, and prevent the decrease in cycle characteristics caused by the decrease in strength.
[0052] <Composition>
[0053] The composition of the polymer is not particularly limited, and can be any composition that can be used as a binder for an all-solid-state battery. The polymer can include, for example, an ethylenically unsaturated acid monomer unit, an alkyl acrylate monomer unit having an alkyl chain with 4 or more carbon atoms, an alkyl methacrylate monomer unit having an alkyl chain with 4 or less carbon atoms, at least one monomer unit selected from a nitrile-containing monomer unit and an aromatic vinyl monomer unit, and other monomer units other than these.
[0054] In the present invention, a polymer "including a monomer unit" means that "a polymer obtained by using the monomer includes a structural unit (repeating unit) derived from the monomer."
[0055] <<Ethylenically unsaturated acid monomer unit>>
[0056] The ethylenically unsaturated acid monomer unit that can be contained in the polymer is a repeating unit from an ethylenically unsaturated acid monomer, contains an ethylenically unsaturated bond and has an acidic group. As the acidic group, -COOH group (carboxylic acid group); -SO3 group (sulfonic acid group); -PO4H2 (phosphoric acid group) and the like can be cited. Therefore, as the ethylenically unsaturated acid monomer, acidic group-containing monomers such as monomers with carboxylic acid groups, monomers with sulfonic acid groups, and monomers with phosphoric acid groups can be used. In addition, as the acidic group-containing monomer, for example, monomers that can generate the above-mentioned acidic groups by hydrolysis can also be cited. As specific examples of such acidic group-containing monomers, acid anhydrides that can generate carboxylic acid groups by hydrolysis can be cited.
[0057] These monomers can be used alone or in combination of two or more at any ratio.
[0058] Monomers having a carboxylic acid group include, for example, monocarboxylic acids, dicarboxylic acids, anhydrides of dicarboxylic acids, and derivatives thereof. Monocarboxylic acids include, for example, acrylic acid, methacrylic acid, crotonic acid, 2-ethylacrylic acid, isocrotonic acid, and the like. Dicarboxylic acids include, for example, maleic acid, fumaric acid, itaconic acid, methylmaleic acid, and the like. Anhydrides of dicarboxylic acids include, for example, maleic anhydride, acrylic anhydride, methylmaleic anhydride, dimethylmaleic anhydride, and the like. Among them, acrylic acid, methacrylic acid, and itaconic acid are preferred.
[0059] Examples of the monomer having a sulfonic acid group include vinyl sulfonic acid, methylvinyl sulfonic acid, (meth)allyl sulfonic acid, styrene sulfonic acid, 2-sulfoethyl (meth)acrylate, 2-acrylamide-2-methylpropanesulfonic acid, 3-allyloxy-2-hydroxypropanesulfonic acid, and 2-(N-acryloyl)amino-2-methyl-1,3-propane-disulfonic acid. Among them, 2-acrylamide-2-methylpropanesulfonic acid is preferred.
[0060] Examples of the monomer having a phosphoric acid group include 2-(meth)acryloyloxyethyl phosphate, methyl-2-(meth)acryloyloxyethyl phosphate, and ethyl-(meth)acryloyloxyethyl phosphate.
[0061] With the amount of all monomeric units constituting the polymer as 100 mass %, the content ratio of the ethylenically unsaturated acid monomeric unit in the polymer is preferably more than 1.5 mass %, more preferably more than 1.7 mass %, more preferably more than 2.0 mass %, more preferably more than 3.0 mass %, in addition, preferably less than 10 mass %, more preferably less than 8 mass %, more preferably less than 6 mass %. If the content ratio of the ethylenically unsaturated acid monomeric unit in the polymer is more than the above-mentioned lower limit, it is possible to prevent the agglomeration of the binder particles, further improve the adhesion with the electrode active material particles and the solid electrolyte particles, and further improve the cycle characteristics. On the other hand, if the content ratio of the ethylenically unsaturated acid monomeric unit in the polymer is less than the above-mentioned upper limit, it is possible to prevent the ethylenically unsaturated acid monomeric unit from reacting with the solid electrolyte, prevent the increase of the resistance caused by the two reactions, and further improve the output characteristics of the all-solid-state battery.
[0062] <<Alkyl acrylate monomer unit having an alkyl chain having 4 or more carbon atoms>>
[0063] The acrylic acid alkyl ester monomer unit having an alkyl chain having 4 or more carbon atoms is a repeating unit derived from an acrylic acid alkyl ester monomer having an alkyl chain having 4 or more carbon atoms.
[0064] As the alkyl acrylate monomer with an alkyl chain having more than 4 carbon atoms that can form an alkyl acrylate monomer unit with an alkyl chain having more than 4 carbon atoms, there can be mentioned: n-butyl acrylate, tert-butyl acrylate, isobutyl acrylate, n-pentyl acrylate, isopentyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate (n-octyl acrylate, isooctyl acrylate, 2-ethylhexyl acrylate, etc.), nonyl acrylate, isononyl acrylate, decyl acrylate, isodecyl acrylate, undecyl acrylate, dodecyl acrylate, tridecyl acrylate, tetradecyl acrylate, pentadecyl acrylate, hexadecyl acrylate, heptadecyl acrylate, stearyl acrylate, etc. Among them, butyl acrylate and 2-ethylhexyl acrylate are preferred. These compounds can be used alone or in combination of two or more in any proportion.
[0065] With the amount of all monomer units constituting the polymer as 100% by mass, the content ratio of the alkyl acrylate monomer unit with an alkyl chain having more than 4 carbon atoms in the polymer is preferably more than 5% by mass, more preferably more than 10% by mass, further preferably more than 15% by mass, more preferably more than 19% by mass, in addition, preferably less than 40% by mass, preferably less than 30% by mass, more preferably less than 25% by mass. If the content ratio of the alkyl acrylate monomer unit with an alkyl chain having more than 4 carbon atoms in the polymer is more than the above lower limit, it is possible to further prevent the adhesion with the solid electrolyte particles from being reduced and causing the cycle characteristics to be reduced. On the other hand, if it is below the above upper limit, it is possible to further prevent the binder particles from agglomerating and prevent the cycle characteristics from being reduced due to the reduced adhesion with the electrode active material and the solid electrolyte particles.
[0066] <<Alkyl methacrylate monomer unit having an alkyl chain having 4 or less carbon atoms>>
[0067] The methacrylic acid alkyl ester monomer unit having an alkyl chain having 4 or less carbon atoms is a repeating unit derived from a methacrylic acid alkyl ester monomer having an alkyl chain having 4 or less carbon atoms.
[0068] As the methacrylate alkyl ester monomer having an alkyl chain having 4 or less carbon atoms that can form the methacrylate alkyl ester monomer unit having an alkyl chain having 4 or less carbon atoms, there can be mentioned: methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, tert-butyl methacrylate, isobutyl methacrylate, etc. Among them, methyl methacrylate and ethyl methacrylate are preferred, and methyl methacrylate is more preferred. These compounds can be used alone or in combination of two or more in any ratio.
[0069] Taking the amount of all monomer units constituting the polymer as 100% by mass, the content ratio of the alkyl methacrylate monomer unit with an alkyl chain having a carbon number of 4 or less in the polymer is preferably 5% by mass or more, more preferably 7% by mass or more, further preferably 9% by mass or more, further preferably 11.5% by mass or more, in addition, preferably 40% by mass or less, preferably 25% by mass or less, and further preferably 20% by mass or less. If the content ratio of the alkyl methacrylate monomer unit with an alkyl chain having a carbon number of 4 or less in the polymer is above the above lower limit, it is possible to further prevent the aggregation of the binder particles and prevent the cycle characteristics from being reduced due to the reduction in adhesion with the electrode active material and the solid electrolyte particles. In addition, if it is below the above upper limit, it is possible to prevent the binder particles from becoming too hard and prevent the cycle characteristics from being reduced due to the reduction in strength.
[0070] <<At least one monomer unit selected from the group consisting of a nitrile group-containing monomer unit and an aromatic vinyl monomer unit>>
[0071] The at least one monomer unit selected from the group consisting of nitrile group-containing monomer units and aromatic vinyl monomer units is a repeating unit derived from at least one monomer selected from the group consisting of nitrile group-containing monomers and aromatic vinyl monomers.
[0072] -Nitrile-containing monomer unit-
[0073] As the nitrile-containing monomer capable of forming the nitrile-containing monomer unit, α, β-ethylenically unsaturated nitrile monomer can be cited. Specifically, as the α, β-ethylenically unsaturated nitrile monomer, there is no particular limitation as long as it is an α, β-ethylenically unsaturated compound having a nitrile group, and examples thereof include: acrylonitrile; α-halogenated acrylonitrile such as α-chloroacrylonitrile and α-bromoacrylonitrile; α-alkyl acrylonitrile such as methacrylonitrile and α-ethylacrylonitrile, etc. Among them, from the viewpoint of well improving the glass transition temperature of the polymer, acrylonitrile and methacrylonitrile are preferred as nitrile-containing monomers. These compounds can be used alone or in combination of two or more.
[0074] -Aromatic vinyl monomer unit-
[0075] As aromatic vinyl compounds capable of forming aromatic vinyl monomer units, there can be mentioned: styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, tert-butylstyrene, divinylbenzene, N,N-dimethyl-p-aminoethylstyrene, 2,4-dimethylstyrene, N,N-diethyl-p-aminoethylstyrene, 2,4-diethylstyrene, vinylnaphthalene, vinylanthracene, etc. Among them, styrene is particularly preferred from the viewpoint of well improving the glass transition temperature of the polymer. These compounds can be used alone or in combination of two or more in any ratio.
[0076] With the amount of all monomeric units constituting the polymer as 100% by mass, the content ratio of at least one monomeric unit selected from nitrile-containing monomeric units and aromatic vinyl monomeric units in the polymer is preferably 40% by mass or more, more preferably 50% by mass or more, further preferably 60% by mass or more, further preferably 66.25% by mass or more, in addition, preferably 80% by mass or less, more preferably 75% by mass or less, further preferably 70% by mass or less. If the content ratio of at least one monomeric unit selected from nitrile-containing monomeric units and aromatic vinyl monomeric units in the polymer is above the above lower limit, the glass transition temperature of the polymer can be well improved, the binder particles can be further prevented from agglomerating, and the cycle characteristics caused by the reduction of the close adhesion with the electrode active material and the solid electrolyte particles can be prevented from being reduced. In addition, if it is below the above upper limit, the binder particles can be prevented from becoming too hard, and the cycle characteristics caused by the reduction of the strength can be prevented from being reduced.
[0077] <<Crosslinking monomer unit>>
[0078] The crosslinkable monomer unit is a repeating unit derived from a crosslinkable monomer. As a crosslinkable monomer capable of forming a crosslinkable monomer unit, a monomer capable of forming a crosslinked structure when polymerized (wherein, the above-mentioned compound as a "monomer" is not included) can be used. Specifically, there can be mentioned: a crosslinkable group having thermal crosslinkability and a monofunctional monomer having one ethylenically unsaturated bond per molecule, and a polyfunctional monomer having two or more ethylenically unsaturated bonds per molecule. Examples of the crosslinkable group having thermal crosslinkability contained in the monofunctional monomer include an epoxy group, an N-hydroxymethylamide group, an oxetanyl group, and combinations thereof.
[0079] Furthermore, the crosslinkable monomer may be hydrophobic or hydrophilic.
[0080] In the present invention, "hydrophobic" crosslinking monomer means that the crosslinking monomer does not contain a hydrophilic group, and "hydrophilic" crosslinking monomer means that the crosslinking monomer contains a hydrophilic group. Here, the "hydrophilic group" in the crosslinking monomer refers to a carboxylic acid group, a hydroxyl group, a sulfonic acid group, a phosphoric acid group, an epoxy group, a thiol group, an aldehyde group, an amide group, an oxetane group, Oxazoline.
[0081] Examples of the hydrophobic crosslinking monomer include: polyfunctional (meth)acrylates such as allyl (meth)acrylate, ethylene glycol dimethacrylate, ethylene glycol dimethacrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, and trimethylolpropane tri(meth)acrylate; polyfunctional allyl / vinyl ethers such as dipropylene glycol diallyl ether, polyethylene glycol diallyl ether, triethylene glycol divinyl ether, hydroquinone diallyl ether, and tetraallyloxyethane; and divinylbenzene.
[0082] Examples of the hydrophilic crosslinking monomer include vinyl glycidyl ether, allyl glycidyl ether, N-methylolacrylamide, acrylamide, and allylmethacrylamide.
[0083] Among them, as the crosslinking monomer, allyl methacrylate, ethylene glycol dimethacrylate, and allyl glycidyl ether are preferred.
[0084] In addition, these can be used individually or in combination of 2 or more types.
[0085] In the case of 100% by mass of the amount of all monomer units, the content ratio of the cross-linked monomer unit in the polymer is preferably 0.1% by mass or more, more preferably 0.15% by mass or more, more preferably 0.2% by mass or more, more preferably 0.25% by mass or more, in addition, preferably less than 2.0% by mass, more preferably less than 1.0% by mass, and more preferably less than 0.5% by mass. If the content ratio of the cross-linked monomer unit in the polymer is above the above lower limit, the polymer has an appropriate gel structure, so it is possible to further prevent excessive aggregation of the binder particles, prevent the adhesion with the electrode active material and the solid electrolyte particles from being reduced, and prevent the cycle characteristics of the all-solid-state battery from being reduced. In addition, if it is below the above upper limit, it is possible to prevent the binder particles from becoming too hard, and prevent the cycle characteristics from being reduced due to reduced strength.
[0086] <<Other monomer units>>
[0087] The monomer units other than the above-mentioned monomer units are not particularly limited, and examples thereof include repeating units derived from known monomers copolymerizable with the above-mentioned monomers, for example, hydroxyl group-containing monomer units and conjugated diene monomer units.
[0088] Examples of monomers having a hydroxyl group and capable of forming a hydroxyl group-containing monomer unit include: ethylenically unsaturated alcohols such as (meth)allyl alcohol, 3-butene-1-ol, and 5-hexene-1-ol; alkyl alcohol esters of ethylenically unsaturated carboxylic acids such as 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, di-2-hydroxyethyl maleate, di-4-hydroxybutyl maleate, and di-2-hydroxypropyl itaconate; General formula: CH2=CR 1 -COO-(C q H 2q O) p -H (wherein, p represents an integer of 2 to 9, q represents an integer of 2 to 4, R 1 esters of polyalkylene glycol represented by methyl (representing a hydrogen atom or a methyl group) and (meth)acrylic acid; mono(meth)acrylates of dihydroxy esters of dicarboxylic acids such as 2-hydroxyethyl-2'-(meth)acryloyloxyphthalate and 2-hydroxyethyl-2'-(meth)acryloyloxysuccinate; vinyl ethers such as 2-hydroxyethyl vinyl ether and 2-hydroxypropyl vinyl ether; (meth)allyl-2-hydroxyethyl ether, (meth)allyl-2-hydroxypropyl ether, (meth)allyl-3-hydroxypropyl ether, (meth)allyl-2-hydroxybutyl ether, (meth)allyl-3-hydroxybutyl ether, (meth)allyl-4-hydroxybutyl ether, (meth)allyl -6-hydroxyhexyl ether and other alkylene glycol mono(meth)allyl ethers; diethylene glycol mono(meth)allyl ether, dipropylene glycol mono(meth)allyl ether and other polyoxyalkylene glycol mono(meth)allyl ethers; glycerol mono(meth)allyl ether, (meth)allyl-2-chloro-3-hydroxypropyl ether, (meth)allyl-2-hydroxy-3-chloropropyl ether and other (poly)alkylene glycol mono(meth)allyl ethers of halogen and hydroxyl substitution; eugenol, isoeugenol and other polyphenol mono(meth)allyl ethers and halogenated products thereof; (meth)allyl sulfide of alkylene glycol such as (meth)allyl-2-hydroxyethyl sulfide and (meth)allyl-2-hydroxypropyl sulfide, etc. These may be used alone or in combination of two or more at any ratio.
[0089] -Conjugated diene monomer unit-
[0090] Examples of the conjugated diene monomer capable of forming the conjugated diene monomer unit include aliphatic conjugated diene monomers such as 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, substituted straight-chain conjugated pentadienes, substituted and side-chain conjugated hexadienes, etc. These may be used alone or in combination of two or more at any ratio.
[0091] Moreover, when all repeating units in the polymer are 100 mass %, the content ratio of the above-mentioned other repeating units in the polymer used in the present invention is preferably 85 mass % or less, more preferably 80 mass % or less, and further preferably 75 mass % or less.
[0092] <Gel structure>
[0093] The polymer preferably has a gel structure, and more specifically, preferably has a gel percentage of 90% or more. If the gel percentage is 90% or more, the polymer has an appropriate amount of gel structure, and therefore, it is possible to further prevent excessive aggregation of the binder particles and prevent the cycle characteristics of the all-solid-state battery from being reduced due to reduced adhesion with the electrode active material and the solid electrolyte particles. The gel percentage is an indicator of the gel structure of the polymer, and is a value indicating the weight ratio of the components that are insoluble in the organic solvent due to the bonding or entanglement of the polymer chains to the whole. The gel percentage can be controlled by adjusting the amount of the cross-linking monomer used, for example.
[0094] In addition, the gel percentage can be calculated as follows, for example, by immersing the membrane obtained by pressure-pressing the binder particles in tetrahydrofuran (THF) for 24 hours, then filtering with a 200-mesh stainless steel mesh, drying the filtered mesh at 100°C for 1 hour, and dividing the weight increase of the mesh by the weight of the membrane.
[0095] <Polymer Synthesis Method>
[0096] The method for synthesizing the polymer used in the present invention is not particularly limited, and the polymer can be obtained, for example, by polymerizing a monomer composition containing the above-mentioned monomers. In addition, the polymerization can also be carried out in the presence of an optional chain transfer agent (molecular weight modifier).
[0097] Here, the content ratio of each monomer in the monomer composition used for synthesizing the polymer can be determined based on the content ratio of each repeating unit in the polymer.
[0098] The polymerization method is not particularly limited, and any method can be used, such as solution polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc. As the form of the polymerization reaction, for example, any form such as ion polymerization, radical polymerization, and living radical polymerization can be used.
[0099] The case where the emulsion polymerization method is adopted as the polymerization method is described below.
[0100] [Emulsion polymerization method]
[0101] The emulsion polymerization method can be carried out according to a conventional method. In addition, when carrying out the emulsion polymerization, commonly used polymerization auxiliary materials such as an emulsifier, a polymerization initiator, and a chain transfer agent can be used.
[0102] As the emulsifier, any emulsifier can be used as long as the desired copolymer can be obtained, and examples thereof include anionic surfactants, nonionic surfactants, cationic surfactants, and amphoteric surfactants. Among these, anionic surfactants such as alkylbenzene sulfonates, aliphatic sulfonates, higher alcohol sulfates, α-olefin sulfonates, and alkyl ether sulfates can be preferably used.
[0103] The amount of the emulsifier is arbitrary as long as the desired polymer can be obtained, but is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and preferably 10 parts by mass or less, more preferably 5 parts by mass or less, based on 100 parts by mass of the total monomers in the monomer composition.
[0104] As the polymerization initiator used in the polymerization reaction, any polymerization initiator can be used as long as a desired polymer can be obtained, and examples thereof include sodium persulfate (NaPS), ammonium persulfate (APS), potassium persulfate (KPS), and the like.
[0105] In addition, during polymerization, the polymerization system may include a chain transfer agent. As a chain transfer agent, for example, alkyl mercaptans such as n-hexyl mercaptan, n-octyl mercaptan, tert-octyl mercaptan, n-dodecyl mercaptan, tert-dodecyl mercaptan, and n-stearyl mercaptan; xanthate compounds such as dimethyl xanthate disulfide and diisopropyl xanthate disulfide; terpinolene; thiuram compounds such as tetramethyl thiuram disulfide, tetraethyl thiuram disulfide, and tetramethyl thiuram monosulfide; phenol compounds such as 2,6-di-tert-butyl-4-methylphenol and styrenated phenol; allyl compounds such as allyl alcohol; halogenated hydrocarbon compounds such as dichloromethane, dibromomethane, and carbon tetrabromide; thioglycolic acid, thiomalic acid, 2-ethylhexyl thioglycolate, diphenylethylene, and α-methylstyrene dimer. Among them, from the viewpoint of suppressing side reactions, alkyl mercaptan is preferred, and tert-dodecyl mercaptan is more preferred. These may be used alone or in combination of two or more at any ratio.
[0106] When a chain transfer agent is used, the amount of the chain transfer agent used is preferably 0.1 parts by mass or more, more preferably 0.15 parts by mass or more, and preferably 0.6 parts by mass or less, more preferably 0.5 parts by mass or less, based on 100 parts by mass of the total monomers in the monomer composition.
[0107] In addition, as solvents that can be used when the emulsion polymerization method is adopted, aqueous solvents can be cited. Here, aqueous solvents refer to solvents containing water and are not flammable. In addition, within the scope of not damaging the effect of the present invention and obtaining the above-mentioned copolymer, water can be used as a main solvent and mixed with aqueous solvents other than water. As aqueous solvents other than water, ketones, alcohols, glycols, glycol ethers, and ethers can be cited.
[0108] In addition, during the polymerization, seed polymerization may be performed using seed particles. In addition, the polymerization conditions may be arbitrarily selected according to the polymerization method and the type of polymerization initiator.
[0109] The synthesized polymer is preferably a granular polymer dispersed in a solvent and also a granular polymer after drying.
[0110] <Granulation of Binder Pellets>
[0111] The binder particles of the present invention can be obtained by granulating the polymer by a conventionally known method. The granulation method is not particularly limited, and preferably includes a step (A) of granulating a raw material slurry containing the polymer by any granulation method, and optionally also includes a step (B) of adjusting the properties of the obtained particles and other steps.
[0112] <<Process (A)>>
[0113] Step (A) is a step of granulating a raw material slurry containing a polymer to obtain binder particles by using a known granulation method such as spray drying granulation, tumbling layer granulation, compression granulation, stirring granulation, extrusion granulation, crushing granulation, fluidized bed granulation, fluidized bed multifunctional granulation, pulse combustion drying, and melt granulation. In step (A), preferably, a spray dryer of a nozzle method or a sprayer method is used to granulate the raw material slurry, and more preferably, a spray dryer of a sprayer method is used to granulate the raw material slurry.
[0114] In addition, the granulation conditions can be appropriately adjusted according to the desired properties of the binder particles.
[0115] <<Process (B)>>
[0116] Step (B) is a step of adjusting the properties of the particles obtained in step (A). Specifically, in step (B), the average particle size D50 of the binder particles can be adjusted using a known particle size distribution adjustment method such as pulverization or classification.
[0117] <<Other processes>>
[0118] As other steps, there are no particular limitations, and the following steps can be cited, that is, before step (A), the polymer is mixed with other polymers, additives such as plasticizers, and / or solvents as arbitrary components to prepare a raw material slurry. As the solvent, there are no particular limitations, and water etc. can be used. In addition, when the above-mentioned polymers are mixed in the state of a solution or an aqueous dispersion, the solvent of the solution or aqueous dispersion can be used as a solvent.
[0119] As a method for dispersing or dissolving the above components in a solvent, for example, a mixing device such as a ball mill, a sand mill, a bead mill, a pigment disperser, an attritor, an ultrasonic disperser, a homogenizer, a homomixer, or a planetary mixer can be used.
[0120] The solid content concentration and viscosity of the raw material slurry can be appropriately adjusted according to the granulation conditions.
[0121] (Composition for all-solid-state battery)
[0122] The all-solid-state battery composition of the present invention comprises at least the binder particles and solid electrolyte particles of the present invention, and optionally comprises an electrode active material (positive electrode active material or negative electrode active material) and / or a conductive aid, a reinforcing material and other additives. In addition, the solvent content of the all-solid-state battery composition of the present invention is 0.1% by mass or less.
[0123] The composition for all-solid-state batteries of the present invention that does not contain an electrode active material is a composition for a solid electrolyte layer that can be used to form a solid electrolyte layer of an all-solid-state battery. Specifically, the composition for a solid electrolyte layer contains at least the binder particles and solid electrolyte particles of the present invention, and optionally contains additives such as reinforcing materials that perform various functions.
[0124] The composition for all-solid-state batteries of the present invention comprising a positive electrode active material is a composition for a positive electrode active material layer that can be used to form a positive electrode active material layer of an all-solid-state battery. Specifically, the composition for the positive electrode active material layer comprises at least the binder particles, positive electrode active material, and solid electrolyte particles of the present invention, and optionally comprises additives such as conductive additives and reinforcing materials that perform various functions.
[0125] The composition for all-solid-state batteries of the present invention comprising a negative electrode active material is a composition for a negative electrode active material layer that can be used to form a negative electrode active material layer of an all-solid-state battery. Specifically, the composition for the negative electrode active material layer comprises at least the binder particles, negative electrode active material, and solid electrolyte particles of the present invention, and optionally comprises additives such as conductive aids and reinforcing materials that perform various functions.
[0126] <Solid electrolyte particles>
[0127] Solid electrolyte particles are usually pulverized and thus are granular, but not completely spherical but irregular in shape. Usually, the size of the particles is measured by irradiating the particles with laser light and measuring the scattered light. When measuring one particle, the particle size in this case is a value assuming that its shape is spherical. When measuring multiple particles at the same time, the existence ratio of particles of corresponding particle sizes can be expressed as a particle size distribution. The solid electrolyte particles that form the solid electrolyte layer mostly use the value measured by this method, which is shown in the form of an average particle size.
[0128] From the viewpoint of ion conduction resistance in the solid electrolyte layer, the average particle size of the solid electrolyte particles is preferably 0.3 μm or more and 5.0 μm or less. In addition, the average particle size of the solid electrolyte particles is a volume average particle size, which refers to the particle size (D50) at which the cumulative volume calculated from the small diameter side reaches 50% in the particle size distribution (volume basis) measured by laser diffraction.
[0129] In the case of an all-solid-state lithium secondary battery, the solid electrolyte particles are not particularly limited as long as they have lithium ion conductivity, and preferably contain a crystalline inorganic lithium ion conductor or an amorphous inorganic lithium ion conductor.
[0130] Examples of crystalline inorganic lithium ion conductors include Li3N, LISICON (Li 14 Zn(GeO4)4), perovskite-type Li 0.5 La 0.5 TiO3、LIPON(Li 3+y PO 4-x N x )、Thio-LISICON(Li 3.25 Ge 0.25 P 0.75 S4) etc.
[0131] As an amorphous inorganic lithium ion conductor, an amorphous inorganic lithium ion conductor (sulfide solid electrolyte material) containing S (sulfur atom) and having ion conductivity can be cited. Here, in the case where the all-solid-state battery used in the all-solid-state battery composition of the present invention is an all-solid-state lithium ion secondary battery, as the sulfide solid electrolyte material used, a sulfide solid electrolyte material formed using a raw material composition containing Li2S and sulfides of Group 13 to Group 15 elements can be cited. As a method for synthesizing a sulfide solid electrolyte material using such a raw material composition, for example, an amorphization method can be cited. As an amorphization method, for example, a mechanical milling method and a melt quenching method can be cited, among which a mechanical milling method is preferred. This is because the mechanical milling method can be processed at room temperature, and the manufacturing process can be simplified.
[0132] As the above-mentioned elements of Groups 13 to 15, for example, Al, Si, Ge, P, As, Sb, etc. can be cited. In addition, as sulfides of elements of Groups 13 to 15, specifically, Al2S3, SiS2, GeS2, P2S3, P2S5, As2S3, Sb2S3, etc. can be cited. Among them, it is preferred to use sulfides of Groups 14 or 15. In particular, the sulfide solid electrolyte material formed using a raw material composition containing Li2S and sulfides of elements of Groups 13 to 15 is preferably Li2S-P2S5 material, Li2S-SiS2 material, Li2S-GeS2 material or Li2S-Al2S3 material, and more preferably Li2S-P2S5 material. This is because they have excellent Li ion conductivity.
[0133] In addition, the sulfide solid dielectric material preferably has cross-linked sulfur. This is because the ion conductivity is improved by having cross-linked sulfur. In addition, "having cross-linked sulfur" can also be determined by examining, for example, the measurement results based on Raman spectroscopy, the raw material composition ratio, the measurement results based on NMR, etc.
[0134] From the viewpoint of being able to more reliably obtain a sulfide solid electrolyte material having cross-linked sulfur, the molar percentage of Li2S in the Li2S-P2S5 material or the Li2S-Al2S3 material is, for example, in the range of greater than 50% and less than 74%, preferably in the range of greater than 60% and less than 74%.
[0135] In addition, the sulfide solid electrolyte material may be sulfide glass, or may be crystallized sulfide glass obtained by heat treating the sulfide glass. Sulfide glass can be obtained, for example, by the above-mentioned amorphization method. Crystallized sulfide glass can be obtained, for example, by heat treating sulfide glass.
[0136] In particular, the sulfide solid electrolyte material is preferably Li7P3S 11 The crystallized sulfide glass shown is because of its excellent Li ion conductivity. 11 For example, Li2S and P2S5 are mixed in a molar ratio of 70:30, amorphized by a ball mill, thereby synthesizing sulfide glass, and the obtained sulfide glass is heat-treated at 150°C or higher and 360°C or lower, thereby synthesizing Li7P3S 11 .
[0137] In addition, as an amorphous inorganic lithium ion conductor, an amorphous inorganic lithium ion conductor (oxide solid electrolyte material) containing O (oxygen atoms) and having ion conductivity can also be used. Examples of oxide solid electrolyte materials include: Li3N, LISICON (Li 14Zn(GeO4)4), perovskite type (e.g. Li 0.5 La 0.5 TiO3), garnet type (e.g. Li7La3Zr2O 12 )、LIPON(Li 3+y PO 4-x N x )、Thio-LISICON(Li 3.25 Ge 0.25 P 0.75 S4) etc.
[0138] <Positive electrode active material>
[0139] In the case of an all-solid-state lithium secondary battery, the positive electrode active material is a compound that can absorb and release lithium ions. The positive electrode active material is roughly divided into a positive electrode active material composed of an inorganic compound and a positive electrode active material composed of an organic compound.
[0140] Examples of positive electrode active materials composed of inorganic compounds include transition metal oxides, composite oxides of lithium and transition metals, and transition metal sulfides. As the above-mentioned transition metals, Fe, Co, Ni, Mn, etc. can be used. Specific examples of inorganic compounds used as positive electrode active materials include: lithium-containing composite metal oxides such as LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiFePO4, and LiFeVO4; transition metal sulfides such as TiS2, TiS3, and amorphous MoS2; Cu2V2O3, amorphous V2O-P2O5, MoO3, V2O5, and V6O 13 These compounds may be compounds in which a part of the elements is replaced.
[0141] Examples of the positive electrode active material composed of an organic compound include polyaniline, polypyrrole, polyacene, disulfide compounds, polysulfide compounds, N-fluoropyridinium salts, etc. The positive electrode active material may be a mixture of the above-mentioned inorganic compound and an organic compound.
[0142] From the viewpoint of improving battery characteristics such as load characteristics and charge-discharge cycle characteristics, in addition, from the viewpoint of being able to obtain a solid electrolyte secondary battery with a large charge-discharge capacity, and the easy processing of the positive electrode active material layer composition and the processing when manufacturing the positive electrode, the average particle size of the positive electrode active material used in the present invention is usually 0.1 μm or more and 50 μm or less, preferably 1 μm or more and 20 μm or less. The average particle size can be obtained by measuring the particle size distribution by laser diffraction.
[0143] <Negative electrode active material>
[0144] As the negative electrode active material, carbon allotropes such as graphite and coke can be cited. The negative electrode active material composed of the above carbon allotropes can be used in the form of a mixture or a coating with a metal, a metal salt, an oxide, etc. In addition, as the negative electrode active material, oxides and sulfates of silicon, tin, zinc, manganese, iron, nickel, etc.; metallic lithium; lithium alloys such as Li-Al, Li-Bi-Cd, Li-Sn-Vd, lithium transition metal nitrides; silicon dioxide, etc. can be used. In the case of a metal material, a metal foil or a metal plate can be used directly as an electrode, or it can be in a granular form.
[0145] When the negative electrode active material is in a granular form, the average particle size of the negative electrode active material is usually greater than 1 μm and less than 50 μm, preferably greater than 15 μm and less than 30 μm, from the perspective of improving battery characteristics such as initial efficiency, load characteristics, and charge and discharge cycle characteristics.
[0146] <Conductive additive>
[0147] The conductive auxiliary agent is not particularly limited as long as it can impart conductivity, and typical examples thereof include carbon powders such as acetylene black, carbon black, and graphite; and fibers and foils of various metals.
[0148] <Reinforcement materials>
[0149] As the reinforcing material, various inorganic and organic fillers in the form of spheres, plates, rods or fibers can be used.
[0150] <Content of Binder Particles in Solid Electrolyte Layer Composition>
[0151] Relative to 100 parts by weight of solid electrolyte particles, the content of the binder particles of the present invention in the solid electrolyte layer composition is preferably 0.1 parts by weight or more, more preferably 0.5 parts by weight or more, and preferably 10 parts by weight or less, more preferably 7 parts by weight or less, and particularly preferably 5 parts by weight or less. By making the content of the binder particles of the present invention within the above range, the adhesion between the solid electrolyte particles can be maintained, and the movement of lithium ions can be inhibited and the resistance of the solid electrolyte layer can be inhibited from increasing.
[0152] <Content of Binder Particles in Positive Electrode Active Material Layer Composition>
[0153] From the viewpoint of not hindering the battery reaction and preventing the electrode active material from falling off the electrode, the content of the binder particles of the present invention in the positive electrode active material layer composition is preferably 0.1 parts by weight or more, more preferably 0.2 parts by weight or more, and preferably 10 parts by weight or less, more preferably 7 parts by weight or less, relative to 100 parts by weight of the positive electrode active material. By making the content of the binder particles of the present invention within the above range, it is possible not to hinder the battery reaction and prevent the positive electrode active material from falling off the electrode.
[0154] <Mass ratio of positive electrode active material to solid electrolyte particles in the positive electrode active material composition>
[0155] The mass ratio of the positive electrode active material to the solid electrolyte particles is preferably positive electrode active material: solid electrolyte particles = 90: 10 to 50: 50, and more preferably positive electrode active material: solid electrolyte particles = 60: 40 to 80: 20. When the mass ratio of the positive electrode active material is within this range, the following phenomenon can be suppressed: due to the mass ratio of the positive electrode active material being too small, the mass of the positive electrode active material in the battery is reduced, resulting in a decrease in the capacity of the battery. In addition, the following phenomenon can be suppressed: due to the mass ratio of the solid electrolyte particles being too small, sufficient conductivity cannot be obtained, the positive electrode active material cannot be effectively utilized, and the capacity of the battery is reduced.
[0156] <Content of Binder Particles in Negative Electrode Active Material Layer Composition>
[0157] When the negative electrode active material is in a granular form, from the viewpoint of not hindering the battery reaction and preventing the electrode active material from falling off the electrode, the content of the binder particles of the present invention in the composition for the negative electrode active material layer is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, relative to 100 parts by mass of the negative electrode active material, and is preferably 5 parts by mass or less, more preferably 4 parts by mass or less.
[0158] <Mass ratio of negative electrode active material to solid electrolyte particles in negative electrode active material layer composition>
[0159] The mass ratio of the negative electrode active material to the solid electrolyte particles is preferably negative electrode active material: solid electrolyte particles = 90: 10 to 50: 50, and more preferably negative electrode active material: solid electrolyte particles = 60: 40 to 80: 20. When the mass ratio of the negative electrode active material is within this range, the following phenomenon can be suppressed: due to the mass ratio of the negative electrode active material being too small, the mass of the negative electrode active material in the battery decreases, resulting in a decrease in the capacity of the battery. In addition, the following phenomenon can be suppressed: due to the mass ratio of the solid electrolyte particles being too small, sufficient conductivity cannot be obtained, the negative electrode active material cannot be effectively utilized, and the capacity of the battery is reduced.
[0160] <Method for producing a composition for an all-solid-state battery>
[0161] The method for producing the composition for all-solid-state batteries of the present invention is not particularly limited. For example, the powders of the above-mentioned components can be dry mixed by any method. As dry mixing methods, for example, methods using mixing devices such as stirring, oscillating and rotating can be cited. In addition, methods using dispersion and mixing devices such as homogenizers, ball mills, bead mills, planetary mixers, sand mills, roller mills and planetary mixers can be cited. From the viewpoint of being able to suppress the agglomeration of powder particles, it is preferred to use a planetary mixer, a ball mill or a bead mill.
[0162] (All-solid-state battery)
[0163] The all-solid-state battery of the present invention comprises: a positive electrode having a positive electrode active material layer on a current collector, a negative electrode having a negative electrode active material layer on a current collector, and a solid electrolyte layer between these positive and negative electrode active material layers, at least one layer of the positive electrode active material layer, the negative electrode active material layer and the solid electrolyte layer contains the binder particles of the present invention, and preferably all layers contain the binder particles of the present invention.
[0164] <Solid electrolyte layer>
[0165] The solid electrolyte layer can be formed by a powder pressing method in which the powder of the solid electrolyte layer composition is pressed. For example, the solid electrolyte layer is formed by placing the powder of the solid electrolyte layer composition on the surface of the positive electrode active material layer or the negative electrode active material layer, and pressing the obtained laminate along its thickness direction. Alternatively, the solid electrolyte layer formed in the same manner on any release substrate can be peeled off and attached to the positive electrode active material layer or the negative electrode active material layer. The method of placing the solid electrolyte layer composition on the electrode active material layer or the release substrate is not particularly limited, and for example, an electrostatic screen printing method can be used.
[0166] The amount of the powder of the solid electrolyte layer composition to be pressed is not particularly limited, and is such that the thickness of the solid electrolyte layer after the pressing is usually 5 μm to 50 μm, preferably 8 μm to 20 μm.
[0167] From the viewpoint of good battery characteristics, the pressure of the press is preferably 5 MPa or more, more preferably 7 MPa or more, preferably 700 MPa or less, and more preferably 500 MPa or less. There is no particular limitation on the press method, and examples thereof include flat press, roll press, CIP (cold isostatic press), and the like.
[0168] <Positive electrode active material layer>
[0169] The positive electrode active material layer can be formed by a powder pressing method in which the powder of the positive electrode active material layer composition is pressed under pressure. For example, the positive electrode active material layer is formed by configuring the powder of the positive electrode active material layer composition on the surface of the later-described current collector or solid electrolyte layer, and pressing the obtained laminate along its thickness direction. Alternatively, the positive electrode active material layer formed in the same manner on any release substrate can be peeled off and attached to the current collector or solid electrolyte layer. The method of configuring the positive electrode active material layer composition on the current collector, solid electrolyte layer or release substrate is not particularly limited, and electrostatic screen printing, for example, can be used.
[0170] The amount of the powder of the positive electrode active material layer composition to be pressed is not particularly limited, and the amount is such that the thickness of each active material layer after the pressing is usually 5 μm to 300 μm, preferably 10 μm to 250 μm.
[0171] The pressure and method of pressurization may be the same as those in the case of the above-mentioned solid electrolyte layer composition.
[0172] <Negative electrode active material layer>
[0173] When the negative electrode active material is in a granular state, the negative electrode active material layer can be formed by a powder pressing method in which the powder of the negative electrode active material layer composition is pressed. For example, the negative electrode active material layer is formed by placing the powder of the negative electrode active material layer composition on the surface of the later-described current collector or solid electrolyte layer, and pressing the obtained laminate along its thickness direction. Alternatively, the negative electrode active material layer formed in the same manner on any release substrate can be peeled off and attached to the current collector or solid electrolyte layer. The method of placing the negative electrode active material layer composition on the current collector, solid electrolyte layer or release substrate is not particularly limited, and electrostatic screen printing, for example, can be used.
[0174] The amount of the powder of the negative electrode active material layer composition to be pressed is not particularly limited, and the amount is such that the thickness of the negative electrode active material layer after the pressing is usually 5 μm to 300 μm, preferably 10 μm to 250 μm.
[0175] The pressure and method of pressurization may be the same as those in the case of the above-mentioned solid electrolyte layer composition.
[0176] <Current collector>
[0177] The current collector used to form the positive active material layer and the negative active material layer can be any material with conductivity and electrochemical durability, without any particular restrictions. From the viewpoint of heat resistance, metal materials such as iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, platinum, etc. are preferred. Among them, aluminum is particularly preferred as a positive electrode, and copper is particularly preferred as a negative electrode. The shape of the current collector is not particularly limited, and is preferably a sheet with a thickness of about 0.001 to 0.5 mm. In order to improve the bonding strength with the above-mentioned positive / negative active material layer, the current collector is preferably subjected to surface roughening treatment in advance and used. As surface roughening methods, mechanical grinding, electrolytic grinding, chemical grinding, etc. can be cited. In the mechanical grinding method, grinding cloth paper, grindstone, grinding wheel, wire brush with steel wire, etc., which are fixed with abrasive particles, can be used. In addition, in order to improve the bonding strength and conductivity of the current collector and the positive / negative active material layer, an intermediate layer can be formed on the surface of the current collector.
[0178] (Manufacturing method of all-solid-state battery)
[0179] The positive electrode in the all-solid-state battery can be obtained by forming a positive electrode active material layer on a current collector. When the negative electrode and / or the solid electrolyte layer are formed using the all-solid-state battery composition of the present invention, a known positive electrode can be used as the positive electrode.
[0180] For the negative electrode in the all-solid-state battery, when the negative electrode active material is a metal foil or a metal plate, it can be directly used as the negative electrode. In addition, when the negative electrode active material is granular, it can be obtained by forming a negative electrode active material layer on another current collector different from the positive electrode current collector. In the case of forming a positive electrode and / or a solid electrolyte layer using the all-solid-state battery composition of the present invention, a known negative electrode can be used as the negative electrode.
[0181] The solid electrolyte layer in the all-solid-state battery can be obtained by forming a solid electrolyte layer on the positive electrode active material layer or the negative electrode active material layer. When the positive electrode and / or the negative electrode are formed using the all-solid-state battery composition of the present invention, a known solid electrolyte layer can be used as the solid electrolyte layer.
[0182] The all-solid-state battery is not particularly limited, and the positive electrode, the negative electrode, and the solid electrolyte layer can be manufactured by any method and in any order.
[0183] Specifically, all-solid-state batteries can be manufactured by the following methods, for example: (1) a method of preparing a stack consisting of a positive electrode active material layer, an electrolyte layer and a negative electrode active material layer, and then bonding current collectors to both sides of the stack; (2) a method of bonding separately prepared positive electrodes, negative electrodes and solid electrolyte layers; (3) a method of forming a solid electrolyte layer on one electrode and then bonding another electrode; (4) a method of preparing a stack consisting of a positive electrode active material layer, an electrolyte layer and a negative electrode active material layer on a current collector and then bonding another current collector.
[0184] Then, the components of the all-solid-state battery obtained as described above are placed in a battery container and sealed in the current state or after winding, folding, etc. according to the battery shape to obtain an all-solid-state battery. In addition, as needed, porous metal mesh, fuses, PTC components and other overcurrent protection components, guide plates, etc. can be placed in the battery container to prevent the pressure inside the battery from rising and overcharging and discharging. The shape of the battery can be any of coin type, button type, sheet type, cylindrical type, square type, flat type, etc.
[0185] By using the binder particles for all-solid-state batteries or the composition for all-solid-state batteries of the present invention, it is possible to obtain an all-solid-state battery functional layer that can provide an all-solid-state battery with good battery characteristics even in a dry state, and an all-solid-state battery with good battery characteristics.
[0186] Example
[0187] The present invention is described below by giving examples, but the present invention is not limited to these examples. Each property is evaluated by the following method. In addition, unless otherwise specified, parts and % in this embodiment are based on mass.
[0188] <Determination of degree of cohesion>
[0189] Using a powder tester [manufactured by Hosokawa Micron Co., Ltd.], sieves with mesh sizes of 250 μm, 150 μm, and 75 μm were stacked on the upper, middle, and lower sections, respectively. 2 g of the binder particles produced in the examples and comparative examples were placed on the sieve with mesh size of 250 μm in the upper section, and vibration was applied for 60 seconds with a vibration amplitude of 1 mm. After the vibration stopped, the degree of aggregation was calculated using the following formulas 1 to 3.
[0190] 1. (weight of binder particles on 250 μm mesh sieve / 2 g) × 100
[0191] 2. (weight of binder particles on 150 μm mesh sieve / 2 g) × 100 × (3 / 5)
[0192] 3. (weight of binder particles on 75 μm mesh sieve / 2 g) × 100 × (1 / 5)
[0193] The total of the calculated values of the above formulas 1 to 3 is defined as the degree of aggregation (%). The lower the value of the degree of aggregation, the better the fluidity.
[0194] <Measurement of particle size>
[0195] The binder particles prepared in the examples and comparative examples were measured for volume-based cumulative particle size distribution using a laser diffraction / scattering particle size distribution measuring apparatus ("Microtrac MT3200II" manufactured by Nikkiso Co., Ltd.) in a dry manner with a dispersion air pressure of 0.02 MPa. The particle size at which the cumulative volume calculated from the smaller diameter side in the measured particle size distribution reaches 50% was taken as the volume average particle size D50 of the binder particles.
[0196] <Measurement of glass transition temperature>
[0197] 10 mg of the powdered sample of the binder particles manufactured in the embodiments and comparative examples was weighed in an aluminum pan, and the measurement was carried out using a differential thermal analysis measuring device (manufactured by Seiko Nanotech Co., Ltd., product name "EXSTAR DSC6220"), in the measurement temperature range: -100°C to 200°C, with a heating rate of 20°C / min, under the conditions specified in JIS Z8703, to obtain a differential scanning calorimetry (DSC) curve. In addition, an empty aluminum pan was used as a reference. During the heating process, the temperature of the peak shown by the differential signal (DDSC) was calculated as the glass transition temperature. In addition, since multiple peaks were measured, the temperature of the peak showing the largest displacement was taken as the glass transition temperature of the binder particles.
[0198] <Measurement of water content>
[0199] 0.2 g of the binder particles produced in Examples and Comparative Examples were weighed in a measuring container and left at a temperature of 25° C. and a dew point of −60° C. for 24 hours. The moisture content of the binder particles was then measured using a coulometric titration moisture meter by the Karl Fischer method (JIS K-0068 (2001) moisture vaporization method, vaporization temperature 150° C.).
[0200] (Evaluation of battery characteristics)
[0201] <Evaluation of output characteristics>
[0202] The all-solid-state secondary battery of three battery cells manufactured in the embodiment and comparative example was charged to 4.2V by a constant current method of 0.1C, and then discharged to 3.0V at 0.1C to obtain the 0.1C discharge capacity. Next, it was charged to 4.2V at 0.1C, and then discharged to 3.0V at 2C to obtain the 2C discharge capacity. The average value of the 0.1C discharge capacity of the three battery cells was taken as the discharge capacity a, and the average value of the 2C discharge capacity of the three battery cells was taken as the discharge capacity b. The ratio of the discharge capacity b to the discharge capacity a (capacity ratio) was obtained = discharge capacity b / discharge capacity a×100 (%), and evaluated according to the following criteria. The larger the value of the capacity ratio, the better the output characteristics.
[0203] A: Capacity ratio is more than 80%
[0204] B: Capacity ratio is 70% or more and less than 80%
[0205] C: Capacity ratio is 50% or more and less than 70%
[0206] D: Capacity ratio less than 50%
[0207] <Evaluation of cycle characteristics>
[0208] The all-solid-state secondary batteries manufactured in the embodiments and comparative examples were repeatedly charged and discharged at 45°C for 50 cycles as follows: charged from 3V to 4.2V at 0.1C, and then discharged from 4.2V to 3V at 0.1C. The ratio of the 0.1C discharge capacity of the 50th cycle to the 0.1C discharge capacity of the first cycle was calculated as a percentage as the capacity retention rate, and evaluated according to the following criteria. The larger the value of the capacity retention rate, the less the discharge capacity decreases and the better the high-temperature cycle characteristics.
[0209] A: Capacity retention rate is more than 90%
[0210] B: Capacity retention rate is 80% or more and less than 90%
[0211] C: Capacity retention rate is 70% or more and less than 80%
[0212] D: Capacity retention rate is less than 70%
[0213] (Example 1)
[0214] <Preparation of polymer>
[0215] In a reactor equipped with a mechanical stirrer and a condenser, 85 parts of ion exchange water and 0.2 parts of sodium dodecylbenzene sulfonate were added under a nitrogen environment, and then heated to 55° C. while stirring. 0.3 parts of potassium persulfate was made into a 5.0% aqueous solution and added to the reactor. Next, in a container different from the above equipped with a mechanical stirrer, 66.25 parts of acrylonitrile (AN) as a nitrile group-containing monomer, 3 parts of methacrylic acid (MAA) as an ethylenically unsaturated acid monomer, 19 parts of butyl acrylate (BA) as an alkyl acrylate monomer having an alkyl chain of 4 or more carbon atoms, 11.5 parts of methyl methacrylate (MMA) as an alkyl methacrylate monomer having an alkyl chain of 4 or less carbon atoms, and 0.25 parts of allyl methacrylate (AMA) as a crosslinking monomer, as well as 0.6 parts of sodium dodecylbenzenesulfonate, 0.035 parts of tert-dodecyl mercaptan, 0.4 parts of polyoxyethylene lauryl ether and 80 parts of ion exchange water were added under a nitrogen atmosphere, and stirred and emulsified to prepare a monomer mixed solution. Then, while the monomer mixed solution was stirred and emulsified, it was added to the above reactor at a constant speed over 5 hours to react until the polymerization conversion reached 95%, thereby obtaining an aqueous dispersion of the polymer.
[0216] <Granulation and classification of binder particles>
[0217] The obtained aqueous dispersion of the polymer was spray dried using a spray dryer (manufactured by NIRO Corporation, GEA) under the conditions of atomizer: rotating disk type (diameter: 150 mm), rotation speed: 11000 rpm, and hot air temperature (outlet temperature): 100° C. to prepare binder particles. Next, the obtained particles were classified using a predetermined sieve to obtain binder particles having an average particle size D50 adjusted to 50 μm.
[0218] The obtained binder particles had a degree of aggregation of 10%, a moisture content of 3500 ppm, and a glass transition temperature of 86°C.
[0219] <Production of positive electrode active material layer>
[0220] 70 parts of lithium cobalt oxide (number average particle size: 11.5 μm) as positive electrode active material particles, 25.5 parts of sulfide glass composed of Li2S and P2S5 (Li2S / P2S5=70 mol% / 30 mol%, number average particle size: 0.9 μm) as solid electrolyte particles, 2.5 parts of acetylene black as a conductive aid, and 2 parts of the binder particles obtained as described above were mixed for 30 minutes using a planetary mixer to prepare a positive electrode active material layer composition.
[0221] 8.5 mg of the obtained positive electrode active material layer composition was filled into a cylindrical mold having a diameter of 10 mm, and then pressed at 200 MPa in the thickness direction of the layer to produce a positive electrode active material layer.
[0222] <Fabrication of solid electrolyte layer>
[0223] In a glove box under an argon atmosphere (water concentration 0.6 mass ppm, oxygen concentration 1.8 mass ppm), 100 parts of sulfide glass composed of Li2S and P2S5 (Li2S / P2S5=70 mol% / 30 mol%, number average particle size: 0.9 μm) as solid electrolyte particles and 2 parts of the binder particles obtained as described above were mixed and mixed for 30 minutes using a planetary mixer. Thus, a composition for a solid electrolyte layer was prepared.
[0224] 50 mg of the obtained solid electrolyte layer composition was filled into the mold and placed on the positive electrode active material layer, and then pressed at 200 MPa in the thickness direction of the layer to produce a solid electrolyte layer.
[0225] <Production of negative electrode active material layer>
[0226] 65 parts of graphite (number average particle size: 20 μm) as negative electrode active material particles, 31.5 parts of sulfide glass composed of Li2S and P2S5 (Li2S / P2S5=70 mol% / 30 mol%, number average particle size: 0.9 μm) as solid electrolyte particles, 1.5 parts of acetylene black as a conductive aid, and 2 parts of the binder particles obtained as described above were mixed and mixed for 30 minutes using a planetary mixer. Thus, a composition for a negative electrode active material layer was prepared.
[0227] 5.5 mg of the obtained negative electrode active material layer composition was filled into the mold and placed on the solid electrolyte layer, and then pressed at 200 MPa in the thickness direction of the layer to produce a negative electrode active material layer.
[0228] <Manufacturing of all-solid-state secondary batteries>
[0229] The laminate consisting of the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer obtained as described above is taken out from the above mold. Aluminum foil as a positive electrode current collector, the above laminate, and copper foil as a negative electrode current collector are sequentially arranged in the above mold. Then, 200MPa pressure pressing is performed along the thickness direction of the layer to produce an all-solid-state battery. Furthermore, the all-solid-state battery produced as described above is placed in a thermostatic bath set to a temperature of 120°C for 3 hours under a pressure of 60.0MPa, thereby imparting adhesion between the binder particles and the active material particles and the solid electrolyte particles. After heating, the all-solid-state battery is cooled to room temperature (25°C).
[0230] (Example 2)
[0231] The polymer was produced in the same manner as in Example 1 except that 19 parts of 2-ethylhexyl acrylate (2EHA) was used instead of 19 parts of butyl acrylate (BA) as an alkyl acrylate monomer having an alkyl chain of 4 or more carbon atoms. Then, the obtained polymer was granulated and classified in the same manner as above to produce binder particles having an average particle size D50 of 38 μm. The obtained binder particles had a cohesion degree of 10%, a moisture content of 3600 ppm, and a glass transition temperature of 90°C.
[0232] Furthermore, using the binder particles, a composition for an all-solid-state battery (a composition for a positive electrode active material layer, a composition for a solid electrolyte layer, and a composition for a negative electrode active material layer) was prepared in the same manner as in Example 1, and an all-solid-state battery was manufactured.
[0233] (Example 3)
[0234] The polymer was prepared in the same manner as in Example 1 except that 66.25 parts of styrene (St) as an aromatic vinyl monomer was used instead of 66.25 parts of acrylonitrile (AN) as a nitrile-containing monomer. Then, the obtained polymer was granulated and classified in the same manner as above to prepare binder particles having an average particle size D50 of 50 μm. In addition, the obtained binder particles had a cohesion degree of 10%, a moisture content of 3300 ppm, and a glass transition temperature of 83°C. In addition, using the binder particles, the preparation of a composition for an all-solid-state battery (a composition for a positive electrode active material layer, a composition for a solid electrolyte layer, and a composition for a negative electrode active material layer) and the manufacture of an all-solid-state battery were carried out in the same manner as in Example 1.
[0235] (Example 4)
[0236] The average particle size D50 of the binder particles was adjusted to 85 μm, and the preparation of the polymer, binder particles and the composition for the all-solid-state battery (composition for the positive electrode active material layer, composition for the solid electrolyte layer, and composition for the negative electrode active material layer), and the manufacture of the all-solid-state battery were performed in the same manner as in Example 1. In addition, the degree of cohesion of the obtained binder particles was 12%, the water content was 4000 ppm, and the glass transition temperature of the polymer was 86°C.
[0237] (Example 5)
[0238] The average particle size D50 of the binder particles was adjusted to 16 μm, and the preparation of the polymer, binder particles and the composition for the all-solid-state battery (composition for the positive electrode active material layer, composition for the solid electrolyte layer, and composition for the negative electrode active material layer), and the manufacture of the all-solid-state battery were performed in the same manner as in Example 1. In addition, the degree of aggregation of the obtained binder particles was 9.5%, the water content was 4100 ppm, and the glass transition temperature of the polymer was 86°C.
[0239] (Example 6)
[0240] The polymer was prepared in the same manner as in Example 1 except that the amount of methacrylic acid (MAA) added was changed to 2.5 parts, the amount of butyl acrylate (BA) added was changed to 24 parts, the amount of methyl methacrylate (MMA) added was changed to 19 parts, the amount of acrylonitrile (AN) added was changed to 54.3 parts, and the amount of allyl methacrylate (AMA) added was changed to 0.2 parts. Then, the obtained polymer was granulated and classified in the same manner as above to prepare binder particles having an average particle size D50 of 55 μm. In addition, the obtained binder particles had a cohesion degree of 20%, a moisture content of 4200 ppm, and a glass transition temperature of 81°C. In addition, using the binder particles, the preparation of a composition for an all-solid-state battery (a composition for a positive electrode active material layer, a composition for a solid electrolyte layer, and a composition for a negative electrode active material layer) and the manufacture of an all-solid-state battery were carried out in the same manner as in Example 1.
[0241] (Example 7)
[0242] The polymer was prepared in the same manner as in Example 1 except that the amount of methacrylic acid (MAA) added was changed to 5 parts, the amount of allyl methacrylate (AMA) added was changed to 0.4 parts, the amount of butyl acrylate (BA) added was changed to 10 parts, the amount of methyl methacrylate (MMA) added was changed to 7 parts, and the amount of acrylonitrile (AN) added was changed to 77.6 parts. Then, the obtained polymer was granulated and classified in the same manner as above to prepare binder particles having an average particle size D50 of 45 μm. In addition, the obtained binder particles had a cohesion degree of 1.5%, a moisture content of 4500 ppm, and a glass transition temperature of 94°C. In addition, using the binder particles, the preparation of a composition for an all-solid-state battery (a composition for a positive electrode active material layer, a composition for a solid electrolyte layer, and a composition for a negative electrode active material layer) and the manufacture of an all-solid-state battery were carried out in the same manner as in Example 1.
[0243] (Example 8)
[0244] The polymer was prepared in the same manner as in Example 1 except that the amount of butyl acrylate (BA) added was changed to 37 parts, the amount of methyl methacrylate (MMA) added was changed to 15 parts, and the amount of acrylonitrile (AN) added was changed to 44.75 parts. Then, the obtained polymer was granulated and classified in the same manner as above to prepare binder particles having an average particle size D50 of 53 μm. In addition, the degree of cohesion of the obtained binder particles was 25%, the moisture content was 3800 ppm, and the glass transition temperature of the polymer was 68°C. In addition, the preparation of the composition for all-solid-state batteries (composition for positive electrode active material layer, composition for solid electrolyte layer, composition for negative electrode active material layer) and the manufacture of all-solid-state batteries were carried out in the same manner as in Example 1.
[0245] (Example 9)
[0246] The amount of methacrylic acid (MAA) added was changed to 5 parts, the amount of butyl acrylate (BA) added was changed to 9 parts, the amount of methyl methacrylate (MMA) added was changed to 5 parts, and 80.75 parts of methacrylonitrile (MAN) were used instead of 66.25 parts of acrylonitrile (AN). The polymer was produced in the same manner as in Example 1. Then, the obtained polymer was granulated and classified in the same manner as above to produce binder particles having an average particle size D50 of 60 μm. In addition, the degree of cohesion of the obtained binder particles was 25%, the moisture content was 3900 ppm, and the glass transition temperature of the polymer was 110°C. In addition, using the binder particles, the preparation of the composition for all-solid-state batteries (composition for positive electrode active material layer, composition for solid electrolyte layer, composition for negative electrode active material layer) and the manufacture of all-solid-state batteries were carried out in the same manner as in Example 1.
[0247] (Example 10)
[0248] Instead of sulfide glass composed of Li2S and P2S5 as solid electrolyte particles, 100 parts of garnet-type Li7La3Zr2O 12 , except for this, the preparation of the polymer and the all-solid-state battery composition (composition for positive electrode active material layer, composition for solid electrolyte layer, composition for negative electrode active material layer), and the manufacture of the all-solid-state battery were carried out in the same manner as in Example 1. In addition, the obtained binder particles had a cohesion degree of 10%, an average particle size D50 of 50 μm, a moisture content of 4200 ppm, and a glass transition temperature of 86°C for the polymer.
[0249] (Comparative Example 1)
[0250] The polymer was prepared in the same manner as in Example 1 except that the amount of methacrylic acid (MAA) added was changed to 9 parts, the amount of allyl methacrylate (AMA) added was changed to 1.9 parts, the amount of butyl acrylate (BA) added was changed to 5 parts, the amount of methyl methacrylate (MMA) added was changed to 5 parts, and the amount of acrylonitrile (AN) added was changed to 79.1 parts. Then, the obtained polymer was granulated and classified in the same manner as above to prepare binder particles having an average particle size D50 of 55 μm. In addition, the obtained binder particles had a cohesion degree of 0.5%, a moisture content of 3600 ppm, and a glass transition temperature of 105°C. In addition, using the binder particles, the preparation of a composition for an all-solid-state battery (a composition for a positive electrode active material layer, a composition for a solid electrolyte layer, and a composition for a negative electrode active material layer) and the manufacture of an all-solid-state battery were carried out in the same manner as in Example 1.
[0251] (Comparative Example 2)
[0252] The polymer was prepared in the same manner as in Example 1 except that the amount of methacrylic acid (MAA) added was changed to 1.5 parts, the amount of allyl methacrylate (AMA) added was changed to 0.1 parts, the amount of butyl acrylate (BA) added was changed to 40 parts, the amount of methyl methacrylate (MMA) added was changed to 15 parts, and the amount of acrylonitrile (AN) added was changed to 43.4 parts. Then, the obtained polymer was granulated and classified in the same manner as above to prepare binder particles having an average particle size D50 of 48 μm. In addition, the obtained binder particles had a cohesion degree of 45%, a moisture content of 4000 ppm, and a glass transition temperature of 63°C. In addition, using the binder particles, the preparation of a composition for an all-solid-state battery (a composition for a positive electrode active material layer, a composition for a solid electrolyte layer, and a composition for a negative electrode active material layer) and the manufacture of an all-solid-state battery were carried out in the same manner as in Example 1.
[0253] (Comparative Example 3)
[0254] The average particle size D50 of the binder particles was adjusted to 8 μm, and except for this, the preparation of the polymer, binder particles, and the composition for all-solid-state batteries (composition for positive electrode active material layer, composition for solid electrolyte layer, and composition for negative electrode active material layer), and the manufacture of all-solid-state batteries were carried out in the same manner as in Example 1. In addition, the degree of cohesion of the obtained binder particles was 9%, the water content was 4200 ppm, and the glass transition temperature of the polymer was 86°C.
[0255] (Comparative Example 4)
[0256] The average particle size D50 of the binder particles was adjusted to 170 μm, and the preparation of the polymer, binder particles, and the composition for the all-solid-state battery (composition for the positive electrode active material layer, composition for the solid electrolyte layer, and composition for the negative electrode active material layer) and the manufacture of the all-solid-state battery were performed in the same manner as in Example 1. In addition, the degree of cohesion of the obtained binder particles was 13%, the water content was 4100 ppm, and the glass transition temperature of the polymer was 86°C.
[0257] [Table 1]
[0258]
[0259] The meanings of the abbreviations in Table 1 are as follows.
[0260] MAA: Methacrylic acid, BA: Butyl acrylate, MMA: Methyl methacrylate, 2EHA: 2-ethylhexyl acrylate, AN: Acrylonitrile, MAN: Methacrylonitrile, St: Styrene, AMA: Allyl methacrylate
[0261] From the results in Table 1, it can be seen that the output characteristics and cycle characteristics of the all-solid-state battery manufactured by the dry method using the binder particles of Examples 1 to 10, each of which has a cohesion degree and a volume average particle size D50 within a specific range, are both excellent. In contrast, it can be seen that the output characteristics and cycle characteristics of the all-solid-state battery manufactured by the dry method using the binder particles of Comparative Examples 1 to 2, whose cohesion degrees are outside the specific range, and the output characteristics and cycle characteristics of the all-solid-state battery manufactured by the dry method using the binder particles of Comparative Examples 3 to 4, whose volume average particle size D50 is outside the specific range, are both poor.
[0262] Industrial Applicability
[0263] According to the present invention, it is possible to provide binder particles for all-solid-state batteries, compositions for all-solid-state batteries, and functional layers for all-solid-state batteries, and all-solid-state batteries that can produce all-solid-state batteries with excellent battery characteristics even when all-solid-state batteries are manufactured in a dry process.
Claims
1. A binder particle for an all-solid-state battery, which is composed of a polymer, The binder particles for all-solid-state batteries have a degree of aggregation of 1% or more and less than 30%, and a volume average particle size D50 of 10 μm or more and 100 μm or less. The polymer comprises an ethylenically unsaturated acid monomer unit, an alkyl acrylate monomer unit having an alkyl chain with 4 or more carbon atoms, an alkyl methacrylate monomer unit having an alkyl chain with 4 or less carbon atoms, at least one monomer unit selected from a nitrile group-containing monomer unit and an aromatic vinyl monomer unit, and a crosslinking monomer unit. The content ratio of the ethylenically unsaturated acid monomer units in the polymer is 1.5% by mass or more and less than 10% by mass, the content ratio of the alkyl acrylate monomer units having an alkyl chain with 4 or more carbon atoms in the polymer is 5% by mass or more and less than 40% by mass, the content ratio of the alkyl methacrylate monomer units having an alkyl chain with 4 or less carbon atoms in the polymer is 5% by mass or more and less than 40% by mass, the content ratio of the crosslinking monomer units in the polymer is 0.1% by mass or more and less than 2.0% by mass, The cohesion degree of the binder particles for all-solid-state batteries is obtained as follows: using a powder testing machine, sieves with mesh sizes of 250 μm, 150 μm and 75 μm are overlapped on the upper, middle and lower sections respectively, 2 g of binder particles are placed on the sieve with a mesh size of 250 μm in the upper section, and vibration is applied for 60 seconds with an amplitude of 1 mm. After the vibration stops, the cohesion degrees of the binder particles on the sieve with a mesh size of 250 μm, the sieve with a mesh size of 150 μm and the sieve with a mesh size of 75 μm are calculated respectively by the following formulas 1 to 3, and the sum of the calculated values of the following formulas 1 to 3 is taken as the cohesion degree of the binder particles for all-solid-state batteries, and the unit is %, Formula 1. (weight of binder particles on 250 μm mesh sieve / 2 g) × 100, Formula 2. (weight of binder particles on 150 μm mesh sieve / 2 g)×100×(3 / 5), Formula 3. (weight of binder particles on 75 μm mesh sieve / 2 g)×100×(1 / 5).
2. The binder particles for all-solid-state batteries according to claim 1, wherein The glass transition temperature of the polymer is 50° C. or higher and 120° C. or lower.
3. A composition for an all-solid-state battery, comprising solid electrolyte particles and the binder particles for an all-solid-state battery according to claim 1 or 2.
4. The composition for an all-solid-state battery according to claim 3, wherein It also contains electrode active material.
5. The composition for an all-solid-state battery according to claim 4, wherein Also contains a conductive additive. 6 . A functional layer for an all-solid-state battery, which is formed from the composition for an all-solid-state battery according to claim 3 .
7. An all-solid-state battery comprising the functional layer for an all-solid-state battery according to claim 6.
Citation Information
Patent Citations
Contact drive device for solenoid relay
JP1989059691B2
Solid electrolytic composition, electrode sheet for batteries arranged by use thereof, and all-solid type secondary battery
JP2015088486A
Solid electrolyte composition, electrode active substance and production method thereof, battery electrode sheet and manufacturing method thereof, and all-solid-state secondary battery and manufacturing method thereof
WO2016136090A1
Solid-state electrolyte composition, sheet for all-solid-state secondary battery, electrode sheet for all-solid-state second battery and manufacturing method therefor, and all-solid-state secondary battery and manufacturing method therefor
CN108432024A
Electrode body for nonaqueous electrolyte battery and nonaqueous electrolyte battery
JP2012227107A